Descriptions of two new dark-body snake eels of the genus Ophichthus (Anguilliformes, Ophichthidae) from Taiwan - Yusuke Hibino; Hsuan-Ching Ho; Jian-Fu Huang (ZooKeys)
Two new species of dark-body snake eels are described based on specimens collected from Taiwan. Ophichthus kbalanensis sp. nov. has a long tail; dorsal-fin origin above posterior third of pectoral fin; tip of lower jaw anterior to anterior-nostril tube; two simple, pointed protrusions along upper lip; preoperculomandibular pores 6 or 7 + 3; teeth on jaws and vomer mostly uniserial, except for biserial on posterior portion of maxilla and anterior portion of symphysis of dentary; vertebral formula 12-55-153 and median fins with narrow dark margins, except the pale fin origins. Ophichthus multidentis sp. nov. has a dorsal-fin origin well behind gill opening; mainly 4 rows of teeth on jaws; no protrusions along upper lip; a smaller head; mean vertebral formula 24-64-163 and pale median fins. Based on some recent papers and our result, a revised key to species is herein provided.